Anti-Inflammatory Effect of Adipose-Derived Stromal Vascular Fraction on Osteoarthritic Temporomandibular Joint Synoviocytes - Kim, Hyungki (Tissue Eng Regen Med, 2020)
BACKGROUND: Osteoarthritis (OA) in the temporomandibular joint (TMJ) in the TMJ (TMJ-OA) is difficult to treat, and new alternative treatments are needed. Recently, adipose-derived stem cells (ASCs) have been introduced as a promising cell source because of their anti-inflammatory effects. However, the cost and availability of these cells limited broader applications of stem cell therapy. Thus, Thus, stromal vascular fraction (SVF) containing sufficient amount of ASCs at low cost can be an alternative. In this study, we aimed to demonstrate the use of uncultured, optimally isolated SVF for the treatment of TMJ-OA. METHODS: First, we optimized the method of isolation to harvest high-quality SVFs with a large yield of ASCs. Then, we analyzed the quantity of ASCs in the SVF and performed characterization of stem cell homology. Subsequently, to evaluate the anti-inflammatory effect of high-quality SVF, an in vitro study was performed to assess the expression patterns of inflammatory cytokines including prostaglandin E(2) (PGE(2)), IL-6, and CXCL8/IL-8, COX2, TNF, IFN, CCL2/MCP-1 and CCL5/RANTES in co-culture with synoviocytes derived from the synovial fluid in the TMJ-OA patients. RESULTS: The SVF containing approximately 32% ASCs was isolated via the our optimized isolation method. The SVF significantly down-regulated certain inflammatory cytokines such as PGE2, CXCL8/IL-8 in TMJ-OA tissue-derived synoviocytes. CONCLUSION: Although further study is needed, our study suggests that transplantation of adipose tissue-derived SVF cells might be a feasible and a novel therapeutic option for TMJ-OA in the future.